2014
DOI: 10.1111/nep.12187
|View full text |Cite
|
Sign up to set email alerts
|

Myeloperoxidase in chronic kidney disease: Role of visceral fat

Abstract: Visceral fat predicted plasma myeloperoxidase in patients with CKD, but not in healthy controls. Myeloperoxidase was probably contributed by primed and activated neutrophils that had been irritated by visceral fat in patients with CKD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…Results revealed that CKD patients had significant high levels of serum MPO compared to the controls, which is similar to earlier findings (17). Increased level of serum MPO generates numerous oxygen species (OS), and these oxidants play a key role in the formation of atherosclerotic plaque and can promote cardiovascular complications (18).…”
Section: P R O V I S I O N a L L Ysupporting
confidence: 85%
“…Results revealed that CKD patients had significant high levels of serum MPO compared to the controls, which is similar to earlier findings (17). Increased level of serum MPO generates numerous oxygen species (OS), and these oxidants play a key role in the formation of atherosclerotic plaque and can promote cardiovascular complications (18).…”
Section: P R O V I S I O N a L L Ysupporting
confidence: 85%
“…This is in contrast with the report of Capeillere-Blandin et al who showed a significantly higher level of myeloperoxidase in ESKD patients on hemodialysis when compared to non-dialysis CKD patients [40]. Increase in myeloperoxidase after hemodialysis [41], its differential regulation by hemodialysis membrane type [42,43], duration of dialysis, and variation in background variables such as anthropometric measures [44], comorbidities and medication use suggest their confounding rules in myeloperoxidase level [45]. The change in 3-ClY is less frequently studied in CKD.…”
Section: Discussionmentioning
confidence: 88%
“…Recently, a ratio between myeloperoxidase (MPO) and paraoxonase 1 (PON1) was suggested as a competent indicator of HDL functionality (7). Giving that both MPO as a pro-oxidative and pro-inflammatory agent and PON1 as a powerful component of anti-oxidative defense system, are already recognized as important mediators of CKD-associated metabolic disorders (8, 9), it would be important to analyze their relationship in children with CKD and after renal transplantation, as well as their association with HDL subclasses distribution.…”
Section: Introductionmentioning
confidence: 99%